2020
DOI: 10.1038/s41598-020-67673-4
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling antimicrobial and anticancerous behavior of AuNPs and AgNPs moderated by rhizome extracts of Curcuma longa from diverse altitudes of Himalaya

Abstract: conservative remedies have a gray history worldwide and these provide productive and pertinent tools to tackle ailments. Also, the high altitude areas of indian Himalayas with their wealthy biodiversity anchorage around 2000 plant species. Ensuing study demonstrates the synthesis of Silver (Ag) and gold (Au) nanoparticles (nps) and utilizes one of the medicaments Curcuma longa of Indian Himalayas collected from different altitudes. For the same, turmeric rhizome extracts have been prepared from the aforesaid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Some more studies further observed concentration-dependent bactericidal efficacy of AuNPs. It was also demonstrated that AuNPs in the concentration range of 50-300 µg/ml exhibited good zone of inhibition against B. subtilis (15.33+ 0.57 to 20.01+0.01) and E. coli (12.00+0.57 to 16.66+0.57) (58). Similarly, AuNPs were observed to exert bactericidal effect against S. aureus (10.0 to 30.0 mm) and E. coli (16.0 to 25.0 mm) at the concentration of 100-200 µg/ml (50).…”
Section: Ecolimentioning
confidence: 92%
“…Some more studies further observed concentration-dependent bactericidal efficacy of AuNPs. It was also demonstrated that AuNPs in the concentration range of 50-300 µg/ml exhibited good zone of inhibition against B. subtilis (15.33+ 0.57 to 20.01+0.01) and E. coli (12.00+0.57 to 16.66+0.57) (58). Similarly, AuNPs were observed to exert bactericidal effect against S. aureus (10.0 to 30.0 mm) and E. coli (16.0 to 25.0 mm) at the concentration of 100-200 µg/ml (50).…”
Section: Ecolimentioning
confidence: 92%
“…Further, silver ions can link with thiol groups of biomolecules and with phosphorus sulfide compounds, such as when DNA inactivates bacteria. Many studies concerning AgNPs' antimicrobial activity have been published (Alafeef, Moitra, & Pan, 2020; Devanesan, Ponmurugan, AlSalhi, & Al‐Dhabi, 2020; Elmehbad & Mohamed, 2020; Garibo et al, 2020; Rao, Saptami, Venkatesan, & Rekha, 2020; Sharma et al, 2020; Taghavizadeh Yazdi et al, 2020).…”
Section: Agnps: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…The β-asarone is able to retard the metabolic transformations and glucose intolerance, to reduce the body weight, cholesterol level in adipose tissue in mice. The lipid-lowering effect has been observed with water extract of sweet flag [ 844 , 845 ]…”
Section: Health Benefit Potentialmentioning
confidence: 99%